Initial Approach to Self-Compacting Concrete with Raw-Crushed Wind-Turbine Blade: Fresh, CFD and Mechanical Analysis - Manuel Hernando-Revenga; Víctor Revilla-Cuesta; José A. Chica; Vanesa Ortega-López; Juan M. Manso (Applied Sciences)
The production of raw-crushed wind-turbine blade (RCWTB) and its addition to conventionally designed self-compacting Concrete (SCC) enable us to provide a second life to wind-turbine blades. However, SCC containing RCWTB must show proper fresh behavior, an aspect evaluated in this paper both experimentally and through simulations based on computational fluid dynamics (CFD) for RCWTB additions up to 3.0% by volume. In experimental terms, RCWTB reduced the flowability and passing ability of SCC, and slowed SCC flow, although the performance of SCC with 1.5% RCWTB was adequate under free-flow conditions. In terms of modeling, RCWTB did not impact yield stress and increased plastic viscosity. CFD modeling under free flow, regardless of the presence or not of obstacles simulating concrete reinforcement, was successful, especially in the long term. Nevertheless, the modeling of the passing ability was not accurate; precision could be improved by simulating the effect of the individual GFRP fibers within the SCC flow. Finally, the mechanical properties of SCC were negatively impacted by RCWTB, the stitching effect of the GFRP fibers not being effective in an SCC with a conventional design. A specific SCC design when adding RCWTB is therefore needed to advance in the use of this waste in this concrete type.